Intraoperative Ultrasound Guidance in Laparoscopic Adrenalectomy: A Retrospective Analysis of Perioperative Outcomes - Ionela Mihai; Adrian Boicean; Horatiu Dura; Cosmin Adrian Teodoru; Dan Georgian Bratu; Cristian Ichim; Samuel Bogdan Todor; Nicolae Bacalbasa; Alina Simona Bereanu; Adrian Hașegan (Diagnostics)
Background: This study aimed to evaluate the advantages of integrating intraoperative ultrasound (IOUS) into laparoscopic adrenal surgery by assessing its impact on perioperative outcomes and identifying potential complications. Methods: This retrospective study analyzed 128 patients with adrenal gland tumors who underwent a laparoscopic adrenalectomy by comparing those who received intraoperative ultrasound guidance with those who did not. The procedures were performed using either the transperitoneal or the lateral retroperitoneal approach. Results: The IOUS-guided group had significantly lower blood loss (p < 0.001) and a shorter hospitalization duration (p = 0.005) compared with the non-IOUS group. No intraoperative complications were observed in the IOUS group, whereas three complications occurred in the non-IOUS group, including peritoneal breaches and minor liver damage. The retroperitoneal approach demonstrated superior perioperative outcomes, with a shorter operative time (p < 0.001), reduced blood loss (p < 0.001), earlier resumption of oral intake and lower postoperative analgesia requirements (p < 0.001). Conclusions: Intraoperative ultrasound enhanced the surgical precision in laparoscopic adrenalectomy, which reduced the blood loss, shortened the hospital stays and minimized the intraoperative complications.